Dermoscopic Features of Eccrine Porocarcinoma Arising from Hidroacanthoma Simplex - Reiko Suzaki; Takeaki Shioda; Izumi Konohana; Sumiko Ishizaki; Mizuki Sawada; Masaru Tanaka (Dermatology Research and Practice)
Eccrine porocarcinoma is a rare cutaneous neoplasm that mainly affects elderly people and grows slowly over a long period of time but often experiences an accelerated growth phase. Eccrine porocarcinoma may arise de novo or evolve from a pre-existing benign eccrine poroma. We reported a 86-year-old Japanese woman presenting with two reddish-colored pendulated lesions on a keratotic light brown plaque on the right thigh. Dermoscopic examination of the light-brown plaque demonstrated many whitish globular structures in a light-brown background. At the two reddish-colored pendulated lesions, polymorphous and prominent vessel proliferation was observed together with irregularly shaped whitish negative network. Immunohistochemical study demonstrated a positive CEA staining at ductal structures and atypical clear cells of reddish nodules. A diagnosis of eccrine porocarcinoma arising in a pigmented hidroacanthoma simplex was eventually established, and the dermoscopic features of eccrine porocarcinoma from hidroacanthoma simplex was described for the first time.